(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Diarrheas are one among the commonest causes of morbidity and mortality in children in developing countries like India. Children below the age group of 5 years in rural areas and of low socio-economic status are most commonly affected due to various reasons like unprotected water supply, poor personal hygiene, illiteracy and malnutrition. Male children were affected more than female children and the commonest age group involved was 0-5 years. Incidence was common in rural population and in low-socioeconomic group. Escherichia coli was the commonest isolate with an incidence rate of 54% followed by Klebsiella (17%), Pseudomonas, Salmonella(1% each) and mixed infection with Escherichia coli and Klebsiella(6%). Most of the isolates were sensitive to Ciprofloxacin, Norfloxacin and Gentamycin. On follow-up, recovery rate was 95% and mortality rate was observed to be 5%. The isolate and the antibiotic sensitivity pattern help the pediatrician in treating children with complaints of diarrhea.